О ВЛИЯНИИ ВНЕШНИХ ФАКТОРОВ НА ЭКЗОГЕННЫЕ ПРОЦЕССЫ В ЗАПАДНОЙ СИБИРИ - Бронгулеев В.В.Д.; Макаренко А.Г. (My University, 2004)
Amongst the correlation of exogenous processes with the factors affecting their intensity the highest ones are those with the absolute heights, amplitudes of neotectonic movements, and endurance of warm period. The percent of forest cover, having middle correlation with some processes, itself suffers their influence. The total dependence of exogenous processes on 9 external factors, used in this work, differs from relatively high to low: the determination coefficients for thermokarst and cryogenic processes reach up to 77% and 79%, for the density and the dept of erosion dissection they consist 52% and 32% correspondingly, for swamp development - 41%. The analysis of partial correlation gave some additional interesting results, which proved this type of correlation to be very important while investigating the multifactor processes. In some cases (but not in all) it gives more adequate evaluation of real factor impact on exogenous processes intensity.
Keywords: 551.435.06(571.1)